Challenges for people with disabilities during disasters in Bangladesh: an exploratory study in Gaibandha district. Issue 1 (May 2014) - Shakil Mahmud, Mir Hasan; Mahmud, Shakil; Rahman, Azad
Abstract : Bangladesh is a disaster prone country; the impact of floods and cyclones is significantly greater for people with disabilities. A cross sectional prospective survey of 50 people with disabilities was undertaken in Gaibandha district in northern Bangladesh where the poorest and most vulnerable people reside often in reed houses at the confluence of two rivers. It showed that respondents faced unfavourable conditions (44%), psychological effects (24%), physical difficulties (20%), and environmental challenges (12%). The majority (90%) believed that disaster is a curse of God. Sixty percent of respondents claimed there was no advance warning system in their community. Respondents identified specific areas that required more emphasis during a disaster; 36% emphasis on food, 24% drinking water, 20% shelter, 10% relief and 6% an accessible environment. They also emphasized the needs for awareness training, warning systems which they can understand, service coordination, and vocational training post-disaster. The results of this survey highlight the role of the occupational therapist in disaster management and particularly in working with people with disabilities in these circumstances.